Analisis Peningkatan Kualitas Produk Pot Bunga Dengan Metode Six Sigma Di PT. Sumber Mas Buana Perkasa - Pratama, Hendra; Apriliano, Nugroho Dwi (Journal Industrial Manufacturing, 2023)
PT. Sumber Mas Buana Pekasa is a company engaged in manufacturing that produces various types of plastic-based products, one of the products produced is flower pots which are used as household decorations. The problem being faced is regarding defective products produced during the production process which are less stable. Therefore, quality control is needed which aims to reduce the level of defects by using one method, namely Six Sigma with the stages of define, measure, analyze, improve and control (DMAIC) which can determine the characteristics of defective products. This study aims to determine the type of product defect, the factors causing the defect and provide suggestions for improvement, from the calculation of the average sigma value on the Flowerpot product in July-December 2020 of 3.88 and the DPMO value of 11178. The highest type of defect based on data processing Black Spots 27.2%, Striped 24.7%, Not full 24.6%, and Flashing 23.6%. The repair phase is carried out using the 5W+1H method. Keywords: Quality, Six sigma, DMAIC, DPMO, FMEA, 5W+1H.